The Historical and Legal Role of Georgia in 1917-1918 for the Unity of the Caucasus - Zegardeli, Beka (Journal of Law, 2022)
The article is devoted to the issue of the unity of the Caucasus region in 1917-1918. The article discusses and analyzes the historical and legal foundations of formation and dissolution of the Transcaucasian Democratic Federal Republic. It presents problems and challenges that existed in the period under discussion both in Georgia and in Transcaucasia as a whole. The article portrays the unity of the Caucasus region and its relationship with Europe, as well as the possibilities of its constitutional regulation. In the end, the article outlines the importance of the state of Georgia and the historical and legal role of Georgian people in management and leadership of issues of the Caucasus region.